2016
DOI: 10.1186/s40463-016-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and risk perception of oral cavity and oropharyngeal cancer among non-medical university students

Abstract: BackgroundTo assess non-medical university students' knowledge and perceived risk of developing oral cavity and oropharyngeal cancer.MethodsA cross-sectional survey was conducted among non-medical students of a private Midwestern university in the United States in May 2012. Questionnaire assessed demographic information and contained 21 previously validated questions regarding knowledge and perceived risk of developing oral cavity and oropharyngeal cancer. Knowledge scale was categorized into low and high. Ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…6 In this context, primary care physicians and dentists should be encouraged to screen highrisk groups on the basis of lifestyle-related factors, age, or the appearance of oral lesions. 7 Drawing on the association between sociodemographic and lifestyle-related factors with the response time from the appearance of symptoms potentially related to HNC, the present study identified alcohol consumption as the main constant of delayed patient reaction. Indeed, a direct association was found between the response time period from the appearance of a mouth ulcer (or soreness) (P < .001), earache (P ¼ .014), hoarseness (P < .001), or painless lump in the neck (P ¼ .003) and alcohol consumption, and this seemed to apply in both genders.…”
Section: Discussionmentioning
confidence: 83%
“…6 In this context, primary care physicians and dentists should be encouraged to screen highrisk groups on the basis of lifestyle-related factors, age, or the appearance of oral lesions. 7 Drawing on the association between sociodemographic and lifestyle-related factors with the response time from the appearance of symptoms potentially related to HNC, the present study identified alcohol consumption as the main constant of delayed patient reaction. Indeed, a direct association was found between the response time period from the appearance of a mouth ulcer (or soreness) (P < .001), earache (P ¼ .014), hoarseness (P < .001), or painless lump in the neck (P ¼ .003) and alcohol consumption, and this seemed to apply in both genders.…”
Section: Discussionmentioning
confidence: 83%
“…This research generated a bank with 113 items (Figures 1-4) to evaluate the "knowledge about head and neck cancer" in any respondent (or group of respondents). On the other hand, in this research we do not intend to present the result referring to the volunteers who composed the sample: high school students and dental surgeons 6,13,[25][26][27][28] , but use the diversity of their answers, in the calibration process, for the positioning of the items in the "knowledge about head and neck cancer" scale" 20,29,30 . It is a (0,1) scale, in which zero(0) represents the mean and one(1) the standard deviation of the ability of the reference group: the first group of students of the 3 rd year of high school.…”
Section: Resultsmentioning
confidence: 99%
“…In order for the doctor, dental surgeon and other health professionals to diagnose a cancer, in addition to understanding the subject, they must admit the possibility of this disease 1 . Measuring the knowledge of these professionals contributes to the strengthening of policies to combat cancer [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…These gene expression differences are thought to involve mechanisms of cancer tumorigenesis, proliferation, invasion, and metastasis. These differences are further reflected by distinct clinical presentations and responses to treatment modalities [ 13 , 14 , 17 , 21 , 48 57 ]. HPV-positivity is most often determined clinically by p16 overexpression, as an acceptable surrogate marker of this disease.…”
Section: Main Textmentioning
confidence: 99%
“…HPV-positivity is most often determined clinically by p16 overexpression, as an acceptable surrogate marker of this disease. The impact of p16 for diagnostics, prognostics and treatment stratification of OPSCC has highlighted the clinical utility of biomarkers for this disease [ 57 61 ]. In other cancers, novel epigenetic biomarkers have shown an increase in popularity for their potential specificity and biomarker-directed therapy [ 62 ].…”
Section: Main Textmentioning
confidence: 99%